2022
DOI: 10.1021/acssuschemeng.1c06810
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Characterizations of Lytic Polysaccharide Monooxygenase, Which Cooperates Synergistically with Cellulases, from Ceriporiopsis subvermispora

Abstract: Lignocellulose-degrading fungi use various oxidative enzymes to degrade lignocellulosic biomass. Oxidative cleavage of cellulose by AA9 family lytic polysaccharide monooxygenases (LPMOs), LPMO9s, reportedly enhances cellulose depolymerization catalyzed by hydrolytic enzymes. To improve this enhancement, functional and structural understanding of LPMO9s is needed. Here, we recombinantly expressed an LPMO9 of Ceriporiopsis subvermispora, CsLPMO9, in Pichia pastoris. Simultaneous treatment of microcrystalline cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The insect binary LPMO-chitinase system acts synergistically to efficiently digest chitin in the old cuticle during the molting process. In a comparable microbial polysaccharide-degrading system, Nguyen et al 44 recently demonstrated that an LPMO ( Cs LPMO9) from the fungus, Ceriporiopsis subvermispora , together with a commercial cellulase cocktail cooperated synergistically to depolymerize microcrystalline cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…The insect binary LPMO-chitinase system acts synergistically to efficiently digest chitin in the old cuticle during the molting process. In a comparable microbial polysaccharide-degrading system, Nguyen et al 44 recently demonstrated that an LPMO ( Cs LPMO9) from the fungus, Ceriporiopsis subvermispora , together with a commercial cellulase cocktail cooperated synergistically to depolymerize microcrystalline cellulose.…”
Section: Discussionmentioning
confidence: 99%